Effects of dietary α-lipoic acid on carcass characteristics, antioxidant capability and meat quality in Hainan black goats. Issue 1 (2nd January 2017) - Wang, Dingfa; Zhou, Luli; Zhou, Hanlin; Hou, Guanyu; Shi, Liguang
Abstract: The effects of α-lipoic acid (LA) on the carcase characteristics, antioxidant capability and meat quality of Hainan black goat were investigated in the present study. Thirty goats (10.71 ± 0.42 kg) were randomly assigned with three levels of LA in the concentration diet (0, 300, 600 mg/kg). The goats fed for 70 days. The results showed that goats fed the diet containing 600 mg/kg LA had a significantly ( p < .05) higher ADG and better feed conversion rate (FCR) compared with goats offered the basal diet without LA. There were no differences in carcase characteristics among the three treatments. For antioxidant enzymes, glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), total antioxidant capacity (T-AOC) and catalase (CAT) in serum significantly increased ( p < .05) in goats fed with 600 mg/kg LA at day 70. The concentration of malondiadehhyde (MDA) was significantly lower ( p < .05) in serum of goats that received 600 mg/kg LA than in the goats fed diet without LA. Addition level of LA had no significant impact on pH and intramuscular fat (IMF) of l ongissimus dorsi muscle tissue (LM) and semimembranosus muscle tissue (SM) in the goats ( p > .05). However, increasing additional LA in the diet caused a decrease on drip loss and WBSF ( p < .05). Treatment of goats with 600 mg/kg of LA has the lowest drip loss and WBSF. These results indicate that diet supplementation with LA may enhance antioxidant capability, improved the growth performance and meat quality in Hainan black goats.